The Khittah of 1926 Reexamined: Views of the NU in Post-Cipasung Congress - Munhanif, Ali (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
When established in 1926 in Surabaya, Nahdlatul Ulama (NU) is meant as an organization of scholars engaged in the field of socio-religious. Concentration struggles and activities of the organization was shaped in the development of the Indonesian Muslim community in the socio-cultural field such as education, teaching, health care, and economic development of the people. In this framework, then, the scholars and leaders of this organization to formulate a vision NU known as Khittah 1926. After a long period gait for NU deviate from Khittah as outlined, to enter the world of practical politics - join Masjumi, became NU party, the PPP fuse - at Muktamarnya 27th in Situbondo, 1984, KH duet. And KH Abdurrahman Wahid. Ahmad Siddiq managed to bring NU back to Khittah 1926. Decision was meant to remove themselves from the bondage of practical politics and prioritize the development of the Indonesian Muslim community culturally.DOI: 10.15408/sdi.v3i2.808